Degrees of freedom of MIMO interference channel with distributed space-time interference alignment - Tengda YING; Wenjiang FENG; Weiheng JIANG; Guoling LIU; Chunan YAO; Taotao BAO (Tongxin xuebao, 2018)
In the context of K-user MIMO interference channel (IC),achievable degrees of freedom (DoF) were investigated with distributed space-time interference alignment (DSTIA).By precoding with distributed current and outdated channel state information at the transmitters (CSIT),new tradeoff regions between achievable DoF and CSI feedback delay/frequency were achieved for MISO system.The impact of the number of transmit antennas on achievable DoF in the MISO system was analyzed,revealing that DoF results approach to the outer bound as the number of transmit antennas increases.Further,the impact of the number of receive antennas on achievable DoF was characterized,deriving the range of CSI feedback delay that preserves achievable DoF in the MIMO system.Theoretical and numerical analyses show that,the proposed DSTIA scheme can achieve better sum-DoFs by eliminating inter-user interference perfectly,tighten the gap between achievable DoF and outer bound,as well as improve the achievable rate of the system.